Mitigation of land scarcity situation through tenure practices: a study on two selected villages in Jashore district of Bangladesh (International Journal of Agricultural Research, Innovation and Technology, 2021)
Bangladesh is one of the most densely populated countries with immense pressure on agricultural land in rural areas. Mainstream of the rural households depend on either agriculture or its associated activities for their livelihood. However, rural land distribution is highly skewed, majority of them are landless. Under such a land scarce situation, farmers in rural areas have been gradually inclining towards land tenancy. Present study steered to explore the nature and volume of temporary land transaction through tenancy agreement in studied areas and to scrutinize its role in aligning land distribution. In 2017, a total of 166 farmers were randomly selected from two different villages in Jashore district for study. Result of the study administrated that land tenancy practice has been significantly mitigating land disparity among rural farmers. Study also explored that comparatively rich farmers are leaning towards tenant out land and most of these lands tenanted in by the landless and marginal farmers. Consequently, on an average landless farm could significantly increases their cultivable land from 0.01 acre to 0.98 acre compared to the marginal farm 0.31 to 0.73 acres. At the same time, cultivable land of medium farm has decreased as of 3.74 acres to 2.83 acres in studied villages.Int. J. Agril. Res. Innov. Tech. 10(2): 164-169, December 2020